Linkages Between Nutrient Resorption and Ecological Stoichiometry and Homeostasis Along a Chronosequence of Mongolian Pine Plantations - Wang, Kai; Wang, G. Geoff; Song, Lining; Zhang, Risheng; Yan, Tao; Li, Yihang (Frontiers in Plant Science, 2021)
Nutrient resorption is an important strategy for nutrient conservation, particularly under conditions of nutrient limitation. However, changes in nutrient resorption efficiency with stand development and the associated correlations with ecological stoichiometry and homeostasis are poorly understood. To elucidate the feedback between tree nutrient conservation strategies and soil nutrient limitations, we measured the carbon (C), nitrogen (N), and phosphorus (P) concentrations in soil and in green and senesced leaves and calculated N and P resorption efficiency (NRE and PRE) and homeostasis coefficients along a chronosequence of Mongolian pine (Pinus sylvestris var. mongolica) plantations consisting of 12-, 22-, 31-, 42-, 52-, and 59-year-old stands in China’s Horqin Sandy Land. We found that soil organic C and total N concentrations increased, but soil total P and available P concentrations decreased with stand age. Green leaf N concentrations and N:P ratios as well as senesced leaf C:N ratios, NRE, and PRE exhibited patterns of initial increase and subsequent decline with stand age, whereas green leaf C:N ratios and senesced leaf N concentrations and N:P ratios exhibited the opposite pattern. NRE was positively correlated with N concentrations and N:P ratios, but negatively correlated with C:N ratios, in green leaves, whereas the opposite pattern was observed in senesced leaves. PRE was negatively correlated with soil C and N concentrations and C:P and N:P ratios but positively correlated with soil P concentrations. The homeostatic coefficient of N:P was greater when including all stand ages than when including only those younger than 42 years, whereas NRE and PRE decreased after the age of 42 years. These findings indicate that tree growth may change from tending to be N limited to tending to be P limited along the Mongolian pine plantation chronosequence. Nutrient resorption was coupled strongly to tree growth and development, whereas it played a lesser role in maintaining stoichiometric homeostasis across the plantation chronosequence.